2008
DOI: 10.1104/pp.107.111815
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Triggers Phosphatidic Acid Accumulation via Phospholipase D during Auxin-Induced Adventitious Root Formation in Cucumber    

Abstract: Auxin and nitric oxide (NO) play fundamental roles throughout plant life. NO is a second messenger in auxin signal transduction leading to root developmental processes. The mechanisms triggered by auxin and NO that direct adventitious root (AR) formation are beginning to be unraveled. The goal of this work was to study phospholipid (PL) signaling during the auxin-and NO-induced AR formation in cucumber (Cucumis sativus) explants. Explants were labeled with 32 P-inorganic phosphate and treated with the auxins i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
84
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 52 publications
4
84
0
Order By: Relevance
“…The concentrations of the above chemicals used for our experiments were supported by other published results (Pagnussat et al, 2002(Pagnussat et al, , 2003(Pagnussat et al, , 2004Cao et al, 2007b;Xuan et al, 2007). Excised cucumber hypocotyls (5-mm-long segments of the hypocotyl base, where adventitious roots develops; Lanteri et al, 2008) were used for the following determination.…”
Section: Explant Treatmentssupporting
confidence: 62%
See 1 more Smart Citation
“…The concentrations of the above chemicals used for our experiments were supported by other published results (Pagnussat et al, 2002(Pagnussat et al, , 2003(Pagnussat et al, , 2004Cao et al, 2007b;Xuan et al, 2007). Excised cucumber hypocotyls (5-mm-long segments of the hypocotyl base, where adventitious roots develops; Lanteri et al, 2008) were used for the following determination.…”
Section: Explant Treatmentssupporting
confidence: 62%
“…Treatment of phytohormones, including indole acetic acid (IAA), 6-benzyladenine, abscisic acid, and GA, enhanced the accumulation of CSCPK5 transcript in etiolated cucumber cotyledons (Kumar et al, 2004). Recently, it was suggested that, together with nitric oxide (NO), which also increases the activity of CDPK and phospholipase D, IAA plays a role in a signaling pathway that regulates CDPK and phospholipase D activity, leading to cucumber adventitious root formation (Lanteri et al, 2006(Lanteri et al, , 2008.…”
mentioning
confidence: 99%
“…In fact, our own data and other reports suggest that ethylene and jasmonic acid signals may be involved in plant responses to AHLs or plant growthpromoting rhizobacteria stimulation (MorquechoContreras et al, 2010;Shi et al, 2010). The roles of these, as well as other messengers, such as phosphatidic acid and carbon monoxide, have been reported to regulate adventitious root formation in cucumber (Lanteri et al, 2008;Xuan et al, 2008); however, their roles in AHL-induced plant adventitious root formation remain to be investigated in further experiments.…”
Section: The Cross Talk Of H 2 O 2 No and Cgmp May Mediate 3-o-c10mentioning
confidence: 97%
“…ROS produced by PA-Rboh interaction may inhibit ABI1 activity, which is likely another mechanism by which PA regulates stomatal closure. On the other hand, recent evidence shows that NO triggers PA accumulation during auxin-induced adventitious root formation (Lanteri et al, 2008) and elicitor response (Laxalt et al, 2007). Whether such a feedback regulation loop exists in ABAmediated stomatal closure needs to be tested.…”
Section: Pa-rbohs Interaction Suggests a Novel Regulatory Mechanism Fmentioning
confidence: 99%